2022
DOI: 10.3390/pathogens11020264
|View full text |Cite
|
Sign up to set email alerts
|

Novel Quantitative Assay to Describe In Vitro Bovine Mastitis Bacterial Pathogen Inhibition by Non-aureus Staphylococci

Abstract: In this paper, we describe a new quantitative method to evaluate and quantify in vitro growth inhibition of mastitis-related bacteria. Colony-forming units of Staphylococcus (S.) aureus (n = 10), Escherichia (E.) coli (n = 10), and Streptococcus (S.) uberis (n = 10) were quantified after their growth on top of layers of trypticase soy agar (TSA) containing six different concentrations (varying from 102 to 107 CFU/mL) of bovine non-aureus staphylococci (NAS), i.e., S. chromogenes (n = 3) and S. simulans (n = 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…These effects have been related to bacterial secreted mediators such as bacteriocins and other potentially beneficial mechanisms such as priming of the immune system [ 9 , 11 ]. We previously showed that S. chromogenes IM, a bovine-derived mastitis strain, is able to (i) inhibit the in vitro growth of major mastitis pathogens including S. uberis and (ii) colonize the bovine mammary gland in vivo [ 12 , 13 ]. To better understand whether priming the mammary gland with S. chromogenes IM inhibits the growth of S. uberis , mouse experiments were hereafter conducted in which S. chromogenes IM-primed murine mammary glands were challenged with S. uberis .…”
Section: Introduction Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects have been related to bacterial secreted mediators such as bacteriocins and other potentially beneficial mechanisms such as priming of the immune system [ 9 , 11 ]. We previously showed that S. chromogenes IM, a bovine-derived mastitis strain, is able to (i) inhibit the in vitro growth of major mastitis pathogens including S. uberis and (ii) colonize the bovine mammary gland in vivo [ 12 , 13 ]. To better understand whether priming the mammary gland with S. chromogenes IM inhibits the growth of S. uberis , mouse experiments were hereafter conducted in which S. chromogenes IM-primed murine mammary glands were challenged with S. uberis .…”
Section: Introduction Methods and Resultsmentioning
confidence: 99%
“…In the specific case of bovine mastitis, recent insights are suggesting the use of bovine NAS to prime the mammary gland and prevent infection by major mastitis pathogens [ 8 , 9 , 11 ]. In this proof-of-concept study, priming of the mammary gland with S. chromogenes IM, a NAS strain previously characterized and used by our groups in multiple in vitro and in vivo studies [ 5 7 , 12 , 13 , 19 ], was investigated to counteract mastitis caused by the major mastitis pathogen S. uberis in a mouse mastitis model [ 14 , 15 ]. First, the inoculum dose and priming potential of the murine mammary gland by this specific NAS strain were studied.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that, in our study population, the mere presence of NASM on the teat apex was not a significant factor driving the risk of IMI in early lactation cows. Other factors, which could potentially account for NASM's ability to prevent major pathogens IMI, as has been proposed in previous research (Reyher et al, 2012), including the presence of in vitro antimicrobial activity (Braem et al, 2014;Carson et al, 2017;Toledo-Silva et al, 2022).…”
Section: Mammaliicocci and Presence Of Intramammary Infectionsmentioning
confidence: 93%
“…Indeed, the infusion into the mammary gland of NASM has been associated with decreased risk for intramammary infection ( IMI ) with SAU and Streptococcus spp., suggesting a potential protective effect of NASM against these two pathogens (Reyher et al, 2012). In vitro studies using isolates obtained from the mammary gland of dairy cows have shown that NASM are capable of inhibiting the growth of SAU (De Vliegher et al, 2004a; Carson et al, 2017; Toledo-Silva et al, 2022). Using the cross-streak method for inhibitory testing, these studies reported that between 9.1% and 14.3% of the isolates were able to inhibit the growth of SAU (Carson et al, 2017; Toledo-Silva et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in dairy animals with mastitis, biofilms within the udders reduce the effect of antimicrobials and allow microorganisms to evade the innate immune system (Lee et al 2022 ; Pedersen et al 2021 ). Some S. chromogenes strains have been confirmed to display a non-biocidal inhibition of pathogenic biofilms and were able to significantly inhibit S. aureus and NASM biofilm formation in a dose-independent manner and without affecting the viability of bovine cells, these findings reveal a new activity of the udder microflora of healthy animals (Beuckelaere et al 2021 ; de Vliegher et al 2004 ; Isaac et al 2017 ; Toledo-Silva et al 2022 ).…”
Section: Biofilm Formationmentioning
confidence: 96%